Analysis of Table Tennis Forehand Drive Ability in Table Tennis Extracurricular Students - Muridhin, Muridhin; Mushofi, Yuskhil; Afandi, Achmad; Junaidi, Ahmad; Yahya, Alfian; Ernata, Yusvidha (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyze the forehand drive ability in table tennis among students participating in the extracurricular table tennis program at MTs Al-Ittihad. This research is descriptive in nature, meaning it seeks to observe the actual conditions in the field regarding students' forehand drive performance. The population of the study consisted of 20 students enrolled in the table tennis extracurricular program at MTs Al-Ittihad Poncokusumo, Malang Regency. Using proportional random sampling, 17 students were selected as the sample.The data collection instrument used was a forehand drive accuracy test, which required students to hit a target area on the table within a 30-second time frame. The goal was to assess the accuracy of each student’s forehand drive. The data analysis method used in this study was percentage calculation, in accordance with the descriptive approach. The results showed that the students’ table tennis skills, particularly in executing the forehand drive, were in the moderate category based on the assessment and analysis conducted.